Pengaruh Servant Leadership Dan Komitmen Organisasi Terhadap Organization Citizenship Behavior (OCB) Pegawai Pesantren Minhajul Haq Purwakarta - Ismail Ludin; Saepul Mukti (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
Organizational citizenship behavior (OCB) is a work behavior that is highly expected to achieve goals in the organization. In its implementation in the workplace, organizational citizenship behavior can affect the atmosphere of a rigid organization or institution into a pleasant and comfortable atmosphere among fellow employees with a strong teamwork atmosphere. This study aims to determine the effect of servant leadership and organizational commitment on OCB. The research method used in this research is descriptive and verification with a quantitative approach. The subjects studied were employees of the Minhajul Haq Islamic Boarding School with a total sample of 78 people using a stratified random sampling technique. The results showed that partially servant leadership had no significant effect on organizational citizenship behavior. However, simultaneously servant leadership and organizational commitment have a significant influence on the organizational citizenship behavior (OCB) of Minhajul Haq Islamic boarding school employees. Organizational commitment has a more dominant influence which is the accumulation of the influencing variables (51.9%).